The effects of temperature and hatchery-rearing conditions on juvenile Atlantic cod (Gadus morhua) behavior - Theodorou, Panagiotis, 1983- (2010)
Atlantic cod (Gadus morhua) is a demersal gadoid that has been one of the most important species in the North Atlantic fisheries for more than 500 years, with major economic, ecological and cultural significance. However, in the past few decades many of the cod stocks have declined dramatically, because of overfishing and changes in the physical environment with major reorganizations of cod ecosystems. Early in their first year of life Atlantic cod juveniles undergo a transition from pelagic to bottom habitats and become demersal. Depending on habitat type, shoaling and hiding are two of the main strategies used by small fish to reduce predation risk. In the first manuscript shoaling behavior of age 0+ wild and farmed Atlantic cod juveniles was examined in an experimental setting. Specifically, we tested if the process of rearing under aquaculture conditions affects the ability of juveniles to adjust shoal behavior according to the spatial complexity of the experimental environment. Trials were performed in the presence of a predatory cod, in the presence of an age 1+ juvenile and without older fish (control). Our results indicated that wild juveniles were more able to change their shoal behavior according to habitat, aggregating more closely in a simple environment but spreading out in the complex environment with shelters. In contrast, farmed juveniles did not vary their group behavior according to the spatial complexity of the environment. These findings suggest that hatchery-rearing does affect the development of shoaling behavior in age 0+ Atlantic cod juveniles and that hatchery-reared cod may be more vulnerable to predation than wild cod. In a changing environment, behavior allows an organism to adjust to either an internal or external stimuli and is the result of adaptations to environmental variables. Thus, behavior is constantly adapting through direct interaction with physical (e.g. temperature), chemical (e.g. oxygen) and social aspects of the environment to ensure maximum fitness and survival of an ...